An Analysis of Conjunctive Relations Found on Oprah Winfrey’s Speech at Spelman University - Tutut Setyaningrum; Dias Andris Susanto (ETERNAL (English Teaching Journal), 2019)
This study is focused on the Conjunctive Relations found in Oprah Winfrey's speech. In this case, conjunctive relations were analyzed through how Oprah Winfrey realized them. The objectives of this study were (1) to find out types of conjunctive relations found on Oprah Winfrey's speech (2) to find out the dominant type of conjunctive relations found on Oprah Winfrey's speech and what is that mean. To reach those two objectives, the writer used both Halliday and J. R. Martin's theory. There are two categories of conjunction namely external and internal conjunction. Later on, those two categories classified themselves into four types of relations namely additive relation, adversative relation, causal relation, and temporal relation. This study used qualitative design because it is framed in terms of using words instead of numbers. The result showed that there were 106 clauses with conjunctions in Oprah's speech. The internal conjunction found were about 52 clauses, while the external conjunction found were about 16 clauses. Both external and internal conjunction was dominated by the causal relation. The causal relation indicated that Oprah Winfrey used a lot of reasoning because causal relations made her able to convince the audience to believe with her statements. Furthermore, causal relation made her speech seems natural, influential, and emotionally convincing to the hearer.